Trusted Financial Statements A Literature Review - Widyastuti, Tri (Siber Journal of Advanced Multidisciplinary, 2024)
The purpose of this research is to find out how much financial reporting contributes to company sustainability. The findings from this research are that financial reporting greatly influences company operations so that they can survive and develop. The research method uses a literature review study. Descriptive qualitative research methodology was used in this research. The data used in this research comes from previous research which is still relevant to the current investigation. Data was collected from leading academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and Sprott journals.